Anti-corrosion of amphoteric metal enhanced by MAO/corrosion inhibitor composite in acid, alkaline and salt solutions - Sun, Weixiang; Liu, Yupeng; Li, Tinghua; Cui, Siwen; Chen, Shougang; Yu, Qiangliang; Wang, Daoai (Journal of colloid and interface science, 2019)
[Display omitted] An anticorrosive composite coating with enhanced corrosion resistance in acid, alkaline and salt solutions was fabricated by compounding micro- and nanoporous inorganic structure and organic corrosion inhibitor, which was used to improve the corrosion resistance of amphoteric metal and its oxides in various corrosive medium. Micro- and nanoporous structure was prepared by microarc oxidation (MAO) coatings on 2024 aluminium alloy, which was used both as the inorganic anticorrosion coating and the container for organic corrosion inhibitor (M16). Electrochemical impedance spectroscopy, Tafel plots and salt spray resistance were measured to research the anticorrosion performance of the MAO/M16 composite coating. Enhanced corrosion resistance was observed for the MAO/M16 coating compared to the MAO by itself. When the concentration of corrosion inhibitor M16 is at 2 w%, the best anticorrosive properties of the composite coating were obtained. Moreover, the MAO/M16 composite coating showed better corrosion-resistant performance than pure MAO coating and Al alloy substrate in the corrosion environment of 1 M HCl, 0.1 M NaOH and 3.5 w% NaCl solutions, respectively. The enhancement of corrosion resistance for MAO/M16 composite coating was achieved by a unique synergy between the microarc oxidation layer and the corrosion inhibitor. The composite coating indicates its promising applications in acid, alkaline and salt solutions environments and other harsh environments.